STUDI KARAKTERISTIK DAN TINGKAT PENDAPATAN PEDAGANG ANGKRINGAN DI KECAMATAN JATEN KABUPATEN KARANGANYAR TAHUN 2012 - susanto, rias silaning putro (Pendidikan Geografi, 2013)
ABSTRACT. Research purpose : (1) knowing the characteristics of angkringan seller in Jaten Subdistrict in 2012, (2) knowing the income level viewed from the characteristics of angkringan sellers in Jaten Subdistrict in 2012. (3) getting to know the income level viewed from the characteristics of angkringan sellers in Jaten Subdistrict in 2012.This study uses qualitative method with spatial and descriptive analysis. The dependent variabel is the angkringan seller in Jaten Subdistrict in 2012. Meanwhile the independent variables are (1) the characteristics consisting of demography and social economy characteristics, (2) income level of the angkringan sellers. These variables are represented in the forms of table and map covering table and map of demography characteristics, social economy characteristics, and income level characteristics. The data are collected by the technique of observation, documentation, and interview. The data analysis technique covers characteristics analysis with primary data and interview, spatial analysis to find the spread. Based on the result, there are suggested that: 1) the angkringan sellers in mid level income follow the strategy that is used by the angkringan sellers in high level income, (2) the angkringan sellers are developed as appealing factor of culinary tour that can increase the territory income. (3)The angkringan seller are the man with age up 30years and the income higher distric income.Key worda : characteristic, income, angkringan seller.